Oral Health Considerations for Patients With Systemic Diseases: Implications for Dental and Nursing Practice - Alamri, Sultan Mohammed; Alharthi, Malak Khalid; Salawi, Nawal Jubran; Alotaibi, Mansour Awad Mulhaq; Alsenani, Moatsem Eid Saleh; Suliman, Abdulrahman Saud Mohammed Al; Al-Zaini, Lama Khaled; Alanazi, May Ayed; Almutairi, Hanan Salah; Alshahrani, Noura Mohammed; Alwasel, Maha Nasser; Hakami, Sarah Ali Ibrahim (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The demographic shift towards an aging population retaining more teeth, combined with a rising prevalence of chronic systemic diseases, means dental practitioners increasingly treat medically complex patients. This necessitates a move beyond routine care to a model that rigorously accounts for systemic health. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to delineate the critical considerations and protocols required for the safe and effective delivery of dental care to patients with systemic diseases, emphasizing a collaborative, interprofessional approach between dental and nursing professionals. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The approach involves a comprehensive synthesis of current evidence and guidelines. It advocates for a structured process integrating meticulous medical history-taking, medication reconciliation, and patient-specific risk stratification using tools like the ASA classification and Charlson Comorbidity Index. The methods highlight the need to interpret how conditions like cardiovascular disease, diabetes, and immunosuppression interact with dental procedures. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The analysis confirms that even minor dental interventions can precipitate significant systemic consequences in vulnerable patients. Key findings provide specific guidance on managing patients with hypertension, coagulopathies, and those undergoing cancer therapy or taking medications like antiresorptives and immunosuppressants. Successful outcomes are shown to depend on interdisciplinary coordination, robust local hemostasis, and staged care to avoid interrupting essential medical therapies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Safe dental care for medically complex patients is achievable through a dynamic, patient-centered model grounded in comprehensive assessment, evidence-based risk mitigation, and seamless collaboration between dentists, nurses, and physicians.